Alcohol-related disorders and associated factors in a rural area in Brazil - Gustavo Pêgas Jaeger; Christian Loret de Mola; Mariangela Freitas Silveira (Revista de Saúde Pública, 2018)
ABSTRACT OBJECTIVE To describe the prevalence of alcohol-related disorders and associated factors in an exclusively rural population. METHODS This is a cross-sectional, population-based study of a rural research consortium, conducted in a medium-sized city in Southern Brazil, with adults living in a rural area, using the AUDIT (Alcohol Use Disorders Identification Test). The analysis included the prevalence of alcohol-related disorders and associated factors, such as the sociodemographic, family, and health factors; it was carried out by Poisson regression, in a hierarchical analysis model, with a 95% confidence interval. RESULTS The final sample amounted to 1,519 subjects. The prevalence of alcohol-related disorders (AUDIT ≥ 8) was 8.4% (95%CI 7.0–9.8). Risk factors for alcohol-related disorders were being male (PR = 8.2, 95%CI 4.82–14.16), age group between 18 and 29 years (PR = 3.29, 95%CI 1.80–6.0), and smoking (PR = 1.88, 95%CI 1.03–3.43). The practice of religion (PR = 0.38, 95%CI 0.25–0.58) and education level between nine and 11 years (PR = 0.33, 95%CI 0.16–0.69) were protective factors with statistical significance. Marital status and social status were not associated with the outcome studied. CONCLUSIONS The prevalence of alcohol-related disorders in the rural population is high, but, on average, it is lower than that found in urban populations. Risk and protective factors were similar to those found in previous studies. Men, younger persons, and smokers are at higher risk for alcohol-related disorders. On the other hand, practicing a religion and having a higher education level were protective factors.